Caracterização funcional e tecnológica de Lactobacillus spp. isolados de grãos de Kefir como critério de seleção de linhagens probióticas - Mário Abatemarco Júnior (2014)
Kefir grains are plenty of lactic acid bacteria in their microbial composition, particularly Lactobacillus. The current use of these microorganisms in food combined with the absence of virulence factors make them interesting as potential probiotics. The objective of this study was to evaluate probiotic characteristics of 52 lactobacilli isolated from milk or sugary kefir grains, by checking the tolerance to simulated conditions of the gastrointestinal tract (gastric juice and bile salts), evaluating the antimicrobial susceptibility profile, antagonistic capacity against pathogenic bacteria and cell surface hydrophobicity. After these tests, ten isolates were selected and lyophilized in the presence of different cryoprotectants, with subsequent evaluation of the survival and in vitro reactivation abilities during 30 days of storage under refrigeration. The number of viable cells after 30 days ranged between cultures tested. The presence of cryoprotectants contributed to maintenance of viability in number higher than 108 cfu/g in eight isolates and resulted in enhanced capacity for reactivation of all lyophilized cultures. After 180 days of storage, the number of viable cells of L. satsumensis 18P-A remained higher than 109 cfu/g, even in the absence of cryoprotectant. The population of L. satsumensis 23P3-L only remained above 109UFC/g until 120 days in the presence of cryoprotectants. Regarding the ability to reactivate after 120 days of storage, lyophilized L. satsumensis 18P-A showed growth as good as fresh culture with all cryoprotectants, what did not happened with L. satsumensis 23P3-L. The in vitro antagonistic activity of L.satsumensis 18P-A against pathogenic bacteria was not altered by lyophilization, as well as its germfree swiss mice gastrointestinal colonization capacity. The results show that L. satsumensis 18P-A is a strong candidate for use as probiotic. Furthermore, it was demonstrated that isolates of the same species can vary significantly in their probiotic features and/or ability to remain viable throughout the processing and storage conditions, confirming that the assessment of technological and functional aspects should be considered for the selection of probiotic strains of industrial interest.